Poleward currents from coastal altimetry: The west coast of Southern Baja California, Mexico - Valle-Rodríguez, J.; Trasviña-Castro, A. (Advances in space research, 2017)
The west coast of Southern Baja California is subject to intense seasonal variability, presenting lowest temperatures from February to April partly due to the upwelling season but also to cold water advection associated to the California Current. The summer advance of a poleward current is responsible for the coastal temperature maxima. In this work we use a time series of currents from a moored Acoustic Doppler Profiler (ADP) to validate coastal altimetry data, in order to study seasonal and interannual coastal current variability. Almost eleven years of coastal altimetry data (2002–2012) from X-TRACK, 20–40km from the coast, reveal a persistent seasonal poleward flow from July to October and equatorward flow, modulated by mesoscale processes the rest of the year. Near the coast of the peninsula sea level raises towards the coast while the poleward current carries a warm water mass against the climatological wind. It is present from July to October in a coastal band 100km wide from the surface to 80m depth with speeds 0.2–0.3ms−1. The interannual variability observed in this period is unusually weak, compared to the previous decade.